Validation in the care and youth work sectors : thematic report for the 2016 update of the European inventory on validation - (:unkn) unknown (Publications Office of the European Union, 2016)
"Based mainly on data collected for the European inventory, the report explores the rationale for validation and considers the use, awareness and types of validation opportunities and the role of employers/organisations in supporting validation in two sectors. The report compares approaches in the care and youth work sectors, reflecting the different purposes of validation and the extent of its labour market connection, currently stronger in the care sector compared to the youth sector. Evidence from both sectors highlights the way different stages of validation are used and applied to different user groups, indicating potential for wider application of validation practices for different target groups and purposes." (Editor, BIBB-Doku)
Keywords: S 6.4.5 Gesundheits-, Sozial- und Erziehungsberufe; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; Pflegeberuf; Jugendarbeit; Sozialpädagogischer Beruf; Anerkennung; Europäische Union